Meningkatkan minat menghafal Al-Qur’an - Nur Hasan; Aushafil Karimah; Albadri Albadri; Hastiani Hastiani (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2022)
The purpose of this study is to describe the implementation of learning in increasing interest in memorizing the Qur'an by using kinesthetic motion, this type of research used is classroom action research. The results of the study indicate an increase in interest in memorizing the Qur'an. by using the motion method, namely Pre-cycle, the percentage value reached 37.5%. as for the average achievement of the indicators of children are: 4.5. after the action of Cycle I, the percentage value reached 75%. While the average achievement of the indicators achieved by children are: 6. And the Cycle II action, the percentage value reached 87.5%. the average value of the child's indicator achievement is: 7.5. it has been found a comparison of interest in memorizing the Qur'an that children have increased interest in memorizing the Qur'an.